MULTICULTURALISM BASED MODERN PESANTREN MANAGEMENT (CASE STUDY AT SUBULUSSALAM MODERN PESANTREN) - Nana Meily Nurdiansyah (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2020)
The reconstruction of the current education system can be felt with a shift in education and teaching governance. The purpose of this study is to identify and analyze the management of Islamic boarding schools by promoting the system (Islamic Teacher College), this research is pursued through a qualitative approach and using descriptive methods. Based on the results of the study, it was found that the Management of the Modern Subulussalam Islamic Boarding School has a management system characterized by an administrative thinking, administrative behavior, administrative attitude. while the management functions used are based planning, organizing, staffing, actuating, controlling. Cottage Life in all its totality becomes a medium of learning and education. Community-based education: Everything that is heard, seen, felt, done, and experienced by the Students and cottage communities is intended to achieve educational goals. The virtue of multiculturalism education in modern boarding school can also be reflected in terms of curriculum contents, extra and intra activities including awareness of tolerance, moderation of religion towards the diversity of beliefs that students will find in the future as a benchmark to meet real life in a pluralistic society.